Does the addition of fentanyl to ketamine improve haemodynamics, intubating conditions or mortality in emergency department intubation: A systematic review. Issue 5 (15th January 2019) - Ferguson, Ian; Bliss, James; Aneman, Anders
Abstract: Background: Ketamine is an induction agent frequently used for general anaesthesia in emergency medicine. Generally regarded as haemodynamically stable, it can cause hypertension and tachycardia and may cause or worsen shock. The effects of ketamine may be improved by the addition of fentanyl to the induction regime. We conducted a systematic review to identify evidence with regard to the effect of adding fentanyl to an induction regime of ketamine and a paralysing agent on post‐induction haemodynamics, intubating conditions and mortality. Methods: We conducted a search of the Cochrane library, EMBASE, MEDLINE, PROQUEST, OpenGrey and clinical trial registries. Prominent authors were contacted in order to identify additional literature pertinent to the research question. Studies were included if they pertained to intubation of adult patients in the prehospital or emergency department environments and included an induction regime of ketamine and a paralysing agent, with at least one outcome measure of haemodynamics, intubating conditions or mortality. Search results were reviewed by two investigators independently, adjudicated by a third investigator where disagreement occurred. Results: One observational study was identified that partially answered the research question. Discussion: Only one observational study was identified that partially answered the research question. This paper demonstrated that the use of fentanyl as a pretreatment increases the incidence of post‐induction hypotension, a phenomenon that was seen with propofol, midazolam and ketamine. The difference in hypotension between these agents was not statistically significant. The impact of this on patient‐orientated outcomes is unclear.